Iron oxide-Palladium core-shell nanospheres for ferromagnetic resonance-based hydrogen gas sensing. (8th February 2022) - Khan, Shahbaz; Lawler, Nicholas B.; Bake, Abdulhakim; Rahman, Rezoan; Cortie, David; Iyer, K. Swaminathan; Martyniuk, Mariusz; Kostylev, Mikhail
Abstract: Interfaces of ferromagnetic transition metals such as Iron, Cobalt, and Nickel with non-magnetic palladium are of interest due to their unique magnetic and spintronic properties. These interfaces enable ferromagnetic resonance (FMR) based sensing of hydrogen gas. In the present work, we synthesized Fe3 O4 –Pd core-shell nanospheres via a one-pot synthesis method using the thermal decomposition of Fe 3+ acetylacetonate in the presence of a reducing agent to produce the Fe3 O4 core, followed by the reduction of a Pd 2+ precursor to form the pure Pd shell. We found that our in-situ synthesized core-shell nanostructure is magnetically active and shows excellent H2 gas sensing properties. The effect of reversible hydrogen gas absorption on the magnetism of Fe3 O4 –Pd core-shell nanospheres was investigated. The hydrogen-induced ferromagnetic-resonance (FMR) peak shift amounted to 30% of the peak linewidth for the virgin state of the sample. In addition, in the presence of hydrogen gas, we observed a fully reversible decrease in the FMR peak linewidth by about two times. This was accompanied by a nearly doubling of the FMR peak height. Response and recovery times of about 2 and 50 s, respectively, were extracted from the measurements. All the data was collected using a mix of just 3% hydrogen in a nitrogen carrier gas. Highlights: FeO–Pd core-shell nanospheres for the efficient detection of hydrogen gas were employed. A one-pot synthesis method was developed to produce FeO–Pd core-shell nanospheres. The core-shell nanosphere system showed a fast response and recovery times. The nanospheres demonstrated superior FMR signal and reversible change upon hydrogenation.